Human ecology : a guide to information sources - Sargent, Frederick (Detroit : Gale Research Company, 1983)
Frederick Sargent died in early 1980, in the midst of a productive life and many important projects. One of the projects outstanding but essentially complete was this annotated bibliography on human ecology. The major task which remained was to write introductions to each section, stating the definition of that particular part, the rationale behind organizing the material in the specified manner, and reasons for inclusion or exclusion of individual items.
Nature and Scope -- Man-Environment Interactions -- Man-Environment Manipulation -- Environmental Quality -- Community Health -- Health Intervention Strategies.
Includes bibliographical references and index.
Keywords: HUMAN ECOLOGY